Optimal dose of etanercept in the treatment of rheumatoid arthritis - Curtis EM (Dove Medical Press, 2014)
Elizabeth Mary Curtis, Jonathan Lewis MarksDepartment of Rheumatology, University Hospital Southampton, Southampton, Hampshire, UKAbstract: Etanercept (ETN) is one of a number of biological therapies targeting the proinflammatory cytokine tumor necrosis factor-alpha that have demonstrated efficacy in the management of rheumatoid arthritis (RA). As experience has grown, a number of different treatment strategies have been investigated to ascertain the optimal conditions for use of ETN in RA and maximize the clinical gains from therapy. These have included the use of higher- and lower-dose treatment regimens, ETN as a monotherapy or in combination with other nonbiologic disease-modifying antirheumatic drugs, the use of ETN in very early clinical disease, and intraarticular ETN administration for resistant synovitis. Recent trials have focused on phased dose reduction or withdrawal of ETN in patients achieving low disease activity states or clinical remission. This review summarizes existing data regarding the optimal timing of ETN initiation and dosing regimens and also evaluates more recent evidence regarding dose-reduction strategies that offer the possibility of biologic-free remission in RA.Keywords: rheumatoid arthritis, etanercept, biologics, antirheumatic agents, monoclonal antibodies, anti-TNF